2020
DOI: 10.3390/pharmaceutics13010034
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan/Poly-L-lysine/Berberine Nanogels for Impaired Wound Healing

Abstract: Physiological wound healing process can be delayed in the presence of certain pathologies, such as diabetes or cancer. In this perspective, the aim of this study was to design a new nanogel platform of hyaluronan, poly-L-lysine and berberine suitable for wound treatment. Two different nanogel formulations were selected after a first formulation screening. They were prepared by adding dropwise 2 mg/mL hyaluronan aqueous solution (200 or 700 kDa) to 1.25 mg/mL poly-L-lysine aqueous solution. Blank nanogels formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…Generating bulk and amorphous hydrogels is the most convenient and widely used fabrication technique for wound dressing applications. Recently, more sophisticated techniques, such as batch emulsion, microfluidic device, extrusion fragmentation, and alternating current (AC) spray have been explored to generate microgels or nanogels hydrogels with tunable size and shape, as well as flexible degradation and mechanical properties ( Sproul et al, 2018 ; Amato et al, 2020 ; Zhao et al, 2020c ; Muir et al, 2021 ; Pan et al, 2021 ). To control hydrogel degradation rate matching with tissue regeneration process, Segura et al developed injectable interconnected microporous hydrogel for which the bulk properties can be controlled through tuning the chemical and physical properties of microgel building blocks generated using a microfluidic device ( Griffin et al, 2015 ).…”
Section: Fabrication Of Hydrogel For Wound Healingmentioning
confidence: 99%
“…Generating bulk and amorphous hydrogels is the most convenient and widely used fabrication technique for wound dressing applications. Recently, more sophisticated techniques, such as batch emulsion, microfluidic device, extrusion fragmentation, and alternating current (AC) spray have been explored to generate microgels or nanogels hydrogels with tunable size and shape, as well as flexible degradation and mechanical properties ( Sproul et al, 2018 ; Amato et al, 2020 ; Zhao et al, 2020c ; Muir et al, 2021 ; Pan et al, 2021 ). To control hydrogel degradation rate matching with tissue regeneration process, Segura et al developed injectable interconnected microporous hydrogel for which the bulk properties can be controlled through tuning the chemical and physical properties of microgel building blocks generated using a microfluidic device ( Griffin et al, 2015 ).…”
Section: Fabrication Of Hydrogel For Wound Healingmentioning
confidence: 99%
“…Experimentation on streptozocin-induced diabetic rats showed that the CA/Gel bandage containing BER promoted wound healing. Furthermore, Amato et al developed a nanogel platform composed of hyaluronan, poly-L-lysine, and BER and evaluated it in vitro [ 52 ]. The results showed that a nanogel loaded with BER could completely close the gap between fibroblasts after 42 h. Interestingly, our developed lecithin–chitosan-based nanoparticulate system loaded with BER was able to speed up the repair process in streptozocin-induced diabetic rats and bring the wound gap to almost complete closure within 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…The cohabitation of the two components, CTS and BER, has a beneficial effect on the wound healing process, as evidenced by the greater wound closure rate in group (D), the group that received BER-LC-CTS-NPs. Both components have been shown to aid in wound healing [ 14 , 20 , 23 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…also reported a modification of hyaluronic acid. By adding a polylysine, novel physically bound nanogels were formed [210] . Nanogels present a greater surface area to volume ratio, and increased potential interactions within in vivo components, in comparison to their bulk counterparts [211] .…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…By adding a polylysine, novel physically bound nanogels were formed. [210] Nanogels present a greater surface area to volume ratio, and increased potential interactions within in vivo components, in comparison to their bulk counterparts. [211] Berberine was incorporated within the hyaluronic acid-polylysine nanogel for its anti-inflammatory and antioxidant properties, as well as its ability to effectively load into the hydrogel.…”
Section: Wound Healingmentioning
confidence: 99%